2019
DOI: 10.32604/jrm.2019.07735
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Dilute Organic Acid Pretreatment and a Comprehensive Exploration of Citric Acid Pretreatment on Corn Cob

Abstract: As an important agricultural waste, corn cob is one of the most abundant lignocellulosic biomass. In this work, dilute acid pretreatment using seven different organic acids were compared for compositional analysis of corn cob. The first pKa of organic acids, influenced by the number and type of the side group and distance between two carboxylic groups, played a crucial role in the pretreatment effect. Citric acid was found to have better pretreatment performance than other tested dicarboxylic acids. Under the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Generally, they are divided into four categories, including physical, chemical, physicochemical and biological methods [4]. However, physical pretreatments are not widely used, given the limited effectiveness [5,6]. In recent studies, microwave and ultrasound are also used in the pretreatment process.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, they are divided into four categories, including physical, chemical, physicochemical and biological methods [4]. However, physical pretreatments are not widely used, given the limited effectiveness [5,6]. In recent studies, microwave and ultrasound are also used in the pretreatment process.…”
Section: Introductionmentioning
confidence: 99%
“…Organic acid pretreatment, as an effective alternative to inorganic acid pretreatment, has been demonstrated to have mild conditions, less corrosiveness to equipment, and fewer inhibitory by-products [28]. The overall performances of pretreating corncob with seven organic acids were investigated recently, which indicated that citric acid (CA) pretreatment is a promising method for biomass utilization [29]. Unlike the conventional inorganic acids, mild CAP could prevent excessive destruction of lignocellulose during pretreatment.…”
Section: Chemical Composition Of Reed After Capmentioning
confidence: 99%
“…Formic acid has also been employed to complete the conversion of carbohydrate and lignin in LDM modification [33,34]. Interestingly, a recent study noted due to their increased pKa; dicarboxylic acid has superior catalytic performance than monocarboxylic acid [35]. As a result, critic acid, a tricarboxylic acid, performed better in modification than the other dicarboxylic acids examined, such as oxalic acid.…”
Section: Organic Acid Modificationmentioning
confidence: 99%
“…As a result, critic acid, a tricarboxylic acid, performed better in modification than the other dicarboxylic acids examined, such as oxalic acid. Organic acids have recently been proposed as possible replacements for inorganic acids in order to prevent product degradation and acquire additional xylan sugars [35]. 93.4% of enzymatic hydrolysis was achieved when corn cob was treated with citric acid at 160℃ for 60 mins.…”
Section: Organic Acid Modificationmentioning
confidence: 99%